Neoadjuvan radyoterapi uygulanan rektum kanseri hastalarında mesane duvarı ve volümü dozlarının karşılaştırılması - ALKIŞ, HİLAL; ADLI, MUSTAFA (My University, 2022)
Purpose/Objective(s): To dosimetrically compare the bladder doses obtained from whole bladder volume and bladder wall only in neoadjuvant radiotherapy of locally advanced rectal cancer (LARC). Materials/Methods: Treatment planning CT images of 65 LARC patients (M/F: 41/24) treated with neoadjuvant radiotherapy were used. Median patient age was 60 (33-82). CT simulation images were taken in supine position with full bladder using iv contrast, with 3.75 mm slice thickness in all patients. Tumor location was proximal rectum in 2 patients, mid-rectum in 27 and distal rectum in 36. Primary tumor was contoured as GTV. CTV-tumor was covering GTV plus 2 cm proximally and distally, and mezorectum radially. Pelvic great vessels, starting from aortic bifurcation, were contoured with a 0.8 cm margin and pre-sacral and obturator regions were included to create CTV-LNs. Whole bladder (WB) and bladder wall only (BW) were separately contoured for study purpose. Prescribed dose was 50.4 Gy in 1.8 Gy/fx for PTV-LNs and PTV-tumor. All plans were done with VMAT using two full arcs. Maximum dose (Dmax), volumes (%) receiving 40 Gy (V40), 45 Gy (V45) and 50 Gy (V50) for WB and BW were recorded and compared. Paired t-test was used for statistical analysis. P<0.05 was accepted statistically significant. Results: Median GTV length was 8 (5-14) cm. Median GTV and total PTV volumes were 78.4 (30.5-330) and 1133 (784-11451.2) ml, respectively. Median WB and BW volumes were 522.5 (157.7-989.6) and 129.9 (33.2-211.3) ml, respectively. Median Dmax was 53.3 (49.5-54.6) Gy in both WB and BW (p=0.5). V40, V45 and V50 were significantly higher for BW than WB (p<0.0001) (Table). Median BW/WB ratios of V40, V45 and V50 were 1.6 (1.1-2.5), 2 (1.2-3.1) and 2.6 (1.6-3.8), respectively. Table. Median (min-max) whole bladder (WB) and bladder wall only (BW) volumes (ml) and volumes receiving 40 Gy (V40), 45 Gy (V45) and 50 Gy (V50) (%). WB BW Volume 522.5 (157.7-989.6) 129.9 (33.2-211.3) V40 26.7 (8.3-42.6) 42.1 (19.5-60.7) V45 17.5 (4-32.4) 33.8 (11.8-54.5) V50 7.6 (0-17.7) 20.9 (0-42.6) Conclusion: Except maximum bladder dose, bladder doses obtained from whole bladder volume does not represent bladder wall doses in LARC patients treated with neoadjuvant radiotherapy. Further studies are needed to evaluate clinical impact of these results. @font-face {font-family:\"Cambria Math\"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-536870145 1107305727 0 0 415 0;}@font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-536859905 -1073732485 9 0 511 0;}p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:\"; margin:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:\"Times New Roman\",serif; mso-fareast-font-family:\"Times New Roman\";}.MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-family:\"Calibri\",sans-serif; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:\"Times New Roman\"; mso-bidi-theme-font:minor-bidi;}div.WordSection1 {page:WordSection1;}
Keywords: Tıp; Dahili Tıp Bilimleri; Radyasyon Onkolojisi; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Radiation Oncology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; Radyoloji ve Ultrason Teknolojisi; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Radyoloji, Nükleer Tıp ve Görüntüleme; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Radiological and Ultrasound Technology; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Radiology, Nuclear Medicine and Imaging; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine